An epigenetic modifier induces production of 3-(4-oxopyrano)-chromen-2-ones in Aspergillus sp. AST0006, an endophytic fungus of Astragalus lentiginosus - Amorim, Marcelo R. de [UNESP]; Wijeratne, E. M. Kithsiri; Zhou, Shengliang; Arnold, A. Elizabeth; Batista, Andrea N. L.; Batista, Joao M.; Santos, Lourdes C. dos [UNESP]; Gunatilaka, A. A. Leslie (Elsevier B.V., 2020)
Incorporation of the epigenetic modifier suberoylanilide hydroxamic acid (SAHA) into a potato dextrose broth culture of the endophytic fungus Aspergillus sp. AST0006 affected its polyketide biosynthetic pathway providing two new 3-(4-oxopyrano)-chromen-2-ones, aspyranochromenones A (1) and B (2), and the isocoumarin, (-)-6,7-dihydroxymellein (3). Eight additional metabolites (4-11) and two biotransformation products of SAHA (12-13) were also encountered. The planar structures and relative configurations of the new metabolites 1-2 were elucidated with the help of high-resolution mass, 1D and 2D NMR spectroscopic data and the absolute configurations of 1-3 were determined by comparison of experimental and calculated ECD data. Possible biosynthetic pathways to 1 and 2 are presented. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Aspergillus sp. AST0006; Endophytic fungus; Epigenetic modifier; Natural products; Aspyranochromenones A and B